Student workbook for public relations writing: principles in practice - Treadwell, Donald; Treadwell, Jill B (California: Sage Publication, 2005)
Sus temas principales Theorical influences on publis relations writing, sending the message writing for style, flow and credibility, ethical influences on publis relations writing
Incluye bibliografía
Keywords: Mercadeo - Relaciones Publicas